Long-term Clinical Efficacy and Safety of Thalidomide in Patients with Transfusion‑dependent β‑thalassemia Major - Shah, Mudassir; Khawaj, Muhammad Basit; Ali, Majid; Khan, Sher Alam; Osama bin Nazeer; Naqvi, Syeda Aqsa (Indus Journal of Bioscience Research, 2025)
This is a study on thalidomide for transfusion-dependent β-thalassemia in patients aged 8–18 years who fail standard hydroxyurea therapy. This was a single-arm trial conducted over 12 months at Alkhidmat Hajira Hamza Thalassemia Center, Abbottabad, involving 50 participants. Hemoglobin levels increased significantly from 6.2 ± 0.7 g/dL at baseline to 9.2 ± 0.5 g/dL at 12 months, with 80% achieving transfusion independence (p < 0.001). Serum ferritin decreased from 2950 ± 450 ng/mL to 950 ± 250 ng/mL, and transfusion frequency reduced to 0.4 ± 0.2 per month (p < 0.001). Spleen size reduced, and organ congestion improved along with normalization of liver size; hence, reduced hemolysis and controlled hypersplenism. Thalidomide was well tolerated; the side effects were minimal constipation (6%) and fatigue (3%); thromboembolism was reported in 4% but responded to treatment. No adverse impact on kidney or liver function was documented. These results show thalidomide as an effective and cheap therapy for hydroxyurea-resistant TDT, whereby hemoglobin improves, transfusion dependency decreases and iron overload becomes decreased. Further randomized controlled trials are needed to ascertain its long-term efficacy and to establish a further scope of clinical application in β-thalassemia management.